Pendampingan dan Pelatihan Penggunaan Aplikasi Sistem Informasi Gampong dalam Upaya Peningkatan Akurasi Data Gampong di Kabupaten Simeulue Provinsi Aceh - Ihsan Hidayatullah; Mohd Dzakhi Ry; Nurul Fitria; Nurul Kamaly; Helmi; Maghfira Faraidiany (LSM Catimore dan Sahabat, 2026)
Simeulue Regency faces geographical, infrastructure, accessibility, and human resource challenges that lead to low village data accuracy, reflected in its 21st ranking in population data entry throughout Aceh. The Village Information System (SIGAP) application was developed for data integration, but its implementation is hampered by minimal digital literacy and operator training. The objective of this community service is to improve operator capacity and data accuracy through training and direct assistance in using the SIGAP application. The approach used was Participatory Action Research (PAR) with intensive one-on-one mentoring, implemented from June 21 to August 5, 2025. The results demonstrated the effectiveness of the intervention strategy focused on improving human resources, with the main success being a drastic increase in the population data entry ranking of Simeulue Regency from 21st to 1st out of 23 regencies/cities in Aceh. This program proves that intensive training and assistance are strategic steps to realize good governance and support government digitalization efforts at the village level.